Introducing Humans to the Extraterrestrials: the Pioneering Missions of the Pioneer and Voyager Probes - Capova, Klara Anna (Frontiers in Human Dynamics, 2021)
This article gives a brief overview of how human life is represented on the 1972 Pioneer 10 and 1973 Pioneer 11 plaques and on the 1977 Voyager 1 and 2 Golden Records, sent on their journeys to deep space by the U.S. National Aeronautics Space Administration (NASA). Having left the boundaries of the Solar System and moving through interstellar space, the space probes still carry messages with information about their makers and their era. After a description of the two famous American interstellar messages, this article gives a basic introduction to their contents using some of the photographs available in the public domain. The overview includes the visual and audio part of the Voyager message and is focused around the questions for what types of information were included, what methods were used to communicate the information and how were humans introduced to the unknown receiver.